Method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method and application of CuO / CeO2 catalyst

The synthesis of CuO/CeO2 catalysts by rapid fluid mixing method solves the problem of low CO removal efficiency in the hydrogen-rich environment in the prior art, achieves the CO oxidation effect with high selectivity and high conversion rate, and simplifies the preparation process.

CN119909769APending Publication Date: 2025-05-02SHIHEZI UNIVERSITY
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202510276106.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has problems such as low coordination reaction efficiency, harsh reaction conditions, cumbersome preparation steps and long time span in CO removal under hydrogen-rich environment, which limits the large-scale application of CuO/CeO2 catalysts.

Method used

The CuO/CeO2 catalyst was synthesized by the rapid fluid mixing method. By injecting a solution of copper salt and cerium salt into the rapid fluid turbulence reactor, the CuCe-BTC-FNP precursor was generated, and then calcined, a CuO/CeO2 catalyst with high catalytic activity was prepared.

Benefits of technology

High selectivity and high conversion rate in CO oxidation reaction under a hydrogen-rich environment are achieved, the CO conversion rate reaches 100% at 90°C, and the corresponding selectivity is also 100%. The synthesis conditions are simplified and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909769A_ABST
    Figure CN119909769A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of CO catalytic oxidation, and particularly discloses a method for synthesizing a CuO / CeO2 catalyst through a rapid fluid mixing method and application thereof.The method comprises the steps that a copper salt solution A and a cerium salt solution B are put into a rapid fluid turbulence mixing reactor, the flow speed is controlled, a catalyst precursor is prepared after product treatment, the catalyst precursor is put into a muffle furnace, air is introduced for calcination, and the catalyst is prepared; and high selectivity and high conversion rate in CO oxidation reaction in a hydrogen-rich environment are realized. The method provided by the invention also improves the traditional MOF synthesis method, adopts water as a solvent, and reduces the synthesis conditions. The prepared catalyst has high conversion rate and selectivity, the CO conversion rate at 90 DEG C reaches 100%, and the corresponding selectivity is 100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of CO catalytic oxidation, in particular to a method for synthesizing a CuO / CeO2 catalyst by a rapid fluid mixing method and application thereof. Background Art

[0002] Hydrogen, an important chemical raw material closely linked to the development of human society, has shown a continuous growth in demand for hydrogen with the advancement of science and technology and the vigorous development of the global economy, especially in the fields of oil refining, fertilizer production and emerging new energy. At the same time, my country's abundant low-rank coal resources are gradually becoming an important part of the national energy strategy. Faced with the current energy structure of "rich in coal, lacking in oil and little gas" and the high dependence on oil resources, how to efficiently and cleanly utilize low-rank coal resources has become the key to the transformation and upgrading of my country's energy industry. Low-temperature retorting fuel production technology is one of the important ways to efficiently utilize low-rank coal. In the industrial chain of Lanzhou coal-coal tar hydrogenation to oil, the hydrogen production link is undoubtedly the core of the entire process. By finding and optimizing the hydrogen production route, not only can the energy efficiency of the entire industrial chain be improved, but also the production cost can be effectively reduced and the market competitiveness can be enhanced. However, in the actual production process, the removal of trace CO in a hydrogen-rich environment is the key. Pressure swing adsorption, selective oxidation and other technologies can be used to ensure the purity of hydrogen and avoid poisoning of metal catalysts (such as Pt, Pd, Ni, Mo, Co, etc.) in the downstream coal-to-liquid hydrogenation process such as hydrorefining or hydrocracking. In order to improve this process link, catalytic oxidation is favored because of its high efficiency, environmental protection, and good selectivity. The catalytic oxidation method converts harmful CO into harmless CO2 through a specific catalyst, thereby eliminating the poisoning effect of CO on the catalysts in subsequent processes. Non-precious metal oxide catalysts, such as CeO2, are characterized by low cost, good stability, and high catalytic activity.

[0003] Rapid fluid turbulent mixing technology is an innovative preparation method specifically used to produce nanoparticles with high specific surface area, precisely controllable size, excellent interfacial properties and highly stable structure. Compared with traditional intermittent direct mixing methods, rapid fluid turbulent mixing reactors significantly overcome the problem of macroscopic uneven mixing. More importantly, this technology platform has excellent industrial scale-up potential, which means that laboratory-level success can be seamlessly transitioned to large-scale production without sacrificing product quality and performance. By utilizing the unique advantages of rapid fluid turbulent mixing, materials are able to experience severe shear forces and turbulent effects in microchannels, conditions that are essential for the formation of nanoparticles with uniform dispersion and finely controlled size. Therefore, this technology not only improves the preparation efficiency of nanoparticles, but also greatly enriches the physical and chemical properties of the resulting materials, opening up new avenues for the development of high-performance nanomaterials.

[0004] As a type of cerium-based metal organic framework (MOFs) material, Ce-BTC is regarded as a high-quality cerium source for the preparation of high-performance CeO2 due to its unique structure and properties. CeO2 with high catalytic activity can be easily obtained by pyrolyzing Ce-BTC. Previously, researchers have tried to apply Ce-BTC to the field of CO catalytic oxidation to remove CO and have achieved certain results. However, these studies generally face challenges such as low coordination reaction efficiency, harsh reaction conditions, cumbersome preparation steps and long time span, which limits the possibility of large-scale application. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method and application thereof.

[0006] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0007] One of the technical solutions of the present invention is a method for synthesizing a CuO / CeO2 catalyst by a rapid fluid mixing method, comprising the following steps:

[0008] S1. Dissolve copper salt and cerium salt in a molar ratio of 1:0.1 to 1:0.3 in 80 mL of deionized water to form solution A;

[0009] S2, dissolving sodium hydroxide and trimesic acid in a mass ratio of 12:7 in 80 mL of deionized water to form solution B;

[0010] S3. Inject equal volumes of solution A and solution B into a fast fluid turbulent flow reactor for reaction, then take the precipitate generated in the fast fluid turbulent mixing reactor and record it as CuCe-BTC-FNP, then let the CuCe-BTC-FNP precipitate stand, centrifuge and collect the solid; vacuum dry and grind, then place the ground powder in a muffle furnace and calcine for 2 hours to obtain a catalyst, named CuCeO-FNP-Ce1CuX, where X is 0.1 to 0.3.

[0011] Preferably, the copper salt is copper nitrate trihydrate, and the cerium salt is cerium nitrate hexahydrate.

[0012] Furthermore, the flow rates of solution A and solution B injected into the fast fluid turbulent mixing reactor are both 90 mL / min.

[0013] Furthermore, the vacuum drying condition is drying at 80° C. for 12 hours.

[0014] Furthermore, the calcination temperature in the muffle furnace is 500° C., and the heating rate is 5° C. / min.

[0015] The second technical solution of the present invention is a CuO / CeO2 catalyst prepared by the above method.

[0016] The third technical solution of the present invention is the use of a CuO / CeO2 catalyst in catalytic oxidation removal of CO in a hydrogen-rich environment.

[0017] Compared with the prior art, the present invention designs the composition of the bimetallic MOF precursor, and after the catalyst precursor is prepared into a catalyst, high selectivity and high conversion rate in the CO oxidation reaction under a hydrogen-rich environment are achieved. The method of the present invention also improves the traditional MOF synthesis method, uses water as a solvent, and reduces the synthesis conditions. The catalyst prepared by the present invention has a high conversion rate and selectivity, and the CO conversion rate reaches 100% at 90°C, and the corresponding selectivity is also 100%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 :(a) XRD patterns of CuCe-BTC precursors prepared with different copper doping amounts in a rapid fluid turbulent mixing reactor; (b) XRD patterns of CuCe-BTC precursors prepared with different solvents by a solvothermal method.

[0019] Figure 2 :(a) N2 adsorption-desorption curves of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor; (b) BJH pore size distribution diagram of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor.

[0020] Figure 3 :(a) CO conversion rate of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor; (b) CO2 selectivity of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor.

[0021] Figure 4 Diagram of a vortex reactor or a rapid fluid turbulent mixing reactor. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0023] Example 1

[0024] First, 2.5-2.6 g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 44-46 g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) were weighed and dissolved in 80 mL of deionized water to form solution A. Then, 1.2-1.3 g of trimesic acid (H3BTC) and 0.7-0.8 g of sodium hydroxide (NaOH) were weighed and dissolved in another 80 mL of deionized water to form solution B. Then, a fast fluid turbulent mixing reactor (such as Figure 4 As shown in the figure, two 50mL syringes are used. 40mL of solution A and solution B are drawn in two-channel molds respectively. The injection speed of solution A and solution B is set to 90mL / min. The resulting precipitate is CuCe-BTC-FNP, which is repeated once. Then the CuCe-BTC-FNP precipitate is allowed to stand for 1 hour, centrifuged, and the precipitate is washed three times with deionized water. The solid is collected and placed in a vacuum drying oven at 80°C for 12 hours, and the dried solid is fully ground to obtain a catalyst precursor. The ground powder is then placed in a muffle furnace, heated to 500°C at a rate of 5°C / min in air, and calcined for 2 hours. The final sample is named CuCe-BTC-FNP-Ce1Cu0.1 according to the element ratio. The prepared catalyst is reacted, and the measured CO conversion rate and CO2 selectivity are shown in Table 1.

[0025]

[0026] Example 2

[0027] First, 2.5-2.6g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 22-23g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) were weighed and dissolved in 80mL of deionized water to form solution A, and then 1.2-1.3g of trimesic acid (H3BTC) and 0.7-0.8g of sodium hydroxide (NaOH) were weighed and dissolved in another 80mL of deionized water to form solution B. Then, two 50mL syringes of a fast fluid turbulent mixing reactor were taken, and 40mL of A and B solutions were drawn into the two-channel mold respectively. The injection speed of A and B solutions was set to 90mL / min, and the resulting precipitate was CuCe-BTC-FNP, which was repeated once. Then, the CuCe-BTC-FNP precipitate was allowed to stand for 1h, centrifuged, and the precipitate was washed three times with deionized water. The solid was collected and placed in a vacuum drying oven at 80°C for 12h, and the dried solid was fully ground to obtain a catalyst precursor. Then the ground powder was placed in a muffle furnace, heated to 500°C at a rate of 5°C / min in air, and calcined for 2h. The final sample was named CuCe-BTC-FNP-Ce1Cu0.2 according to the element ratio. The prepared catalyst was reacted, and the measured CO conversion rate and CO2 selectivity are shown in Table 2.

[0028]

[0029] Example 3

[0030] First, 2.5-2.6g of copper nitrate trihydrate (Cu(NO3)2·3H2O) and 14.5-15.5g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) were weighed and dissolved in 80mL of deionized water to form solution A, and then 1.2-1.3g of trimesic acid (H3BTC) and 0.7-0.8g of sodium hydroxide (NaOH) were weighed and dissolved in another 80mL of deionized water to form solution B. Then, two 50mL syringes of a fast fluid turbulent mixing reactor were taken, and 40mL of A and B solutions were drawn into the two-channel mold, respectively, and the injection speed of A and B solutions was set to 90mL / min. The resulting precipitate was CuCe-BTC-FNP, which was repeated once. Then, the CuCe-BTC-FNP precipitate was allowed to stand for 1h, centrifuged, and the precipitate was washed three times with deionized water. The solid was collected and placed in a vacuum drying oven at 80°C for 12h, and the dried solid was fully ground to obtain a catalyst precursor. Then the ground powder was placed in a muffle furnace, heated to 500°C at a rate of 5°C / min in air, and calcined for 2h. The final sample was named CuCe-BTC-FNP-Ce1Cu0.3 according to the element ratio. The prepared catalyst was reacted, and the measured CO conversion rate and CO2 selectivity are shown in Table 3.

[0031]

[0032] Comparative Example 1

[0033] The preparation of Ce-BTC was slightly modified based on the reported method. First, 0.70-0.80g of trimesic acid (H3BTC), 2.5-2.7g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and 0.15-0.20g of copper nitrate trihydrate (Cu(NO3)2·3H2O) were weighed and dissolved in 60mL of anhydrous ethanol. Then, the completely dissolved solution was transferred to a 180mL stainless steel autoclave with a Teflon liner, heated to 130°C for 24h of solvent thermal reaction and then cooled naturally. After the autoclave cooled to room temperature, the autoclave was opened, the solution after the reaction was taken out, centrifuged, and the precipitate was washed three times with anhydrous ethanol or N,N-dimethylformamide, the solid was collected, placed in a vacuum drying oven at 80°C for 12h, and the dried solid was fully ground to a certain mesh size to obtain the catalyst precursor CuCe-BTC-ST. Then the ground powder was placed in a muffle furnace, heated to 500°C at a rate of 5°C / min in air, and calcined for 2h. The final sample was named CuCeO-ST-EtOH based on the solvent. The obtained catalyst was reacted, and the measured CO conversion rate and CO2 selectivity are shown in Table 4.

[0034]

[0035] Comparative Example 2

[0036] The preparation of Ce-BTC was slightly modified based on the reported method. First, 0.70-0.80g of trimesic acid (H3BTC), 2.5-2.7g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and 0.15-0.20g of copper nitrate trihydrate (Cu(NO3)2·3H2O) were weighed and dissolved in 60mL of N,N-dimethylformamide. Then, the completely dissolved solution was transferred to a 180mL stainless steel autoclave with a Teflon liner, heated to 130°C for 24h of solvent thermal reaction and then cooled naturally. After the autoclave cooled to room temperature, the autoclave was opened, the solution after the reaction was taken out, centrifuged, and the precipitate was washed three times with anhydrous ethanol or N,N-dimethylformamide, the solid was collected, placed in a vacuum drying oven at 80°C and dried for 12h, and the dried solid was fully ground to a certain mesh size to obtain the catalyst precursor CuCe-BTC-ST. Then the ground powder was placed in a muffle furnace, heated to 500°C at a rate of 5°C / min in air, and calcined for 2h. The final sample was named CuCeO-ST-DMF after the solvent. The obtained catalyst was reacted, and the measured CO conversion rate and CO2 selectivity are shown in Table 5.

[0037]

[0038] The specific experimental steps for the catalyst to convert CO into CO2 are as follows:

[0039] Catalyst loading: Add a certain amount of 16-30 mesh fine quartz sand into the reaction tube to ensure that the catalyst bed is in a constant temperature zone. After adding quartz wool, weigh 0.1g of catalyst powder using an analytical balance and fill it into the reaction tube. Place the reaction tube into the heating furnace, and finally insert a K-type thermocouple probe to contact the catalyst bed, and tighten all connections.

[0040] Catalyst performance test: Turn on nitrogen, wait for the gas mass flow meter to stabilize, and then check the air tightness of the device. Turn on the heating furnace, and heat the temperature from room temperature to 50°C at a nitrogen flow rate of 40mL / min at a heating rate of 5°C / min. After the catalyst bed temperature reaches 50°C, turn off nitrogen, turn on H2 and CO synthesis gas, and adjust the total flow rate of the reaction gas (volume ratio CO / O2 / N2 / H2=1:1:48:50) to 40mL / min, and the space velocity WHSV to 24000mL·g -1 ·h -1The heating furnace was programmed to heat up, and the CO oxidation reaction performance test in a hydrogen-rich atmosphere was carried out. Within the temperature range of 0.1Mpa and 50-200°C, each 25°C was a test temperature point, and each point was kept for about 20 minutes. When the actual reaction temperature was basically the same as the set temperature, sampling and analysis were carried out. Each point was sampled twice, and the gas after the reaction was passed into a GC-2014C Shimadzu gas chromatograph for detection and analysis.

[0041] Figure 1 :(a) XRD patterns of CuCe-BTC precursors prepared with different copper doping amounts in a rapid fluid turbulent mixing reactor; (b) XRD patterns of CuCe-BTC precursors prepared with different solvents by a solvothermal method. Figure 2 :(a) N2 adsorption-desorption curves of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor; (b) BJH pore size distribution diagram of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor. Figure 3 :(a) CO conversion rate of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor; (b) CO2 selectivity of CuO / CeO2 catalysts prepared with different copper doping amounts in a fast fluid turbulent mixing reactor.

[0042] Depend on Figure 1 It can be seen that the curves of the three catalysts are consistent with the typical type IV adsorption of mesoporous materials, and an H3 type hysteresis loop appears. As shown in Table 5-1, as the copper doping ratio increases from 1:0.1 to 1:0.2 and 1:0.3, the copper content of the catalyst increases from 2.7wt.% to 6.6wt.% and 9.5wt.%, respectively, and as the copper doping amount increases, the specific surface area of ​​the catalyst increases first and then decreases. When the cerium-copper ratio is 1:0.2, the specific surface area reaches the maximum value (118.79m 2 / g), the change trend of the average pore volume is consistent with the specific surface area. When the copper doping amount is too high, accumulation and aggregation will occur, which will block part of the pores, causing the specific surface area and pore volume of the catalyst to decrease to a certain extent. Compared with catalysts prepared by other methods, the specific surface area and pore volume of the catalyst are further increased, which may be because the bimetallic MOF precursor can promote the dispersion of the catalyst metal active sites, thereby better improving the catalyst's catalytic activity for CO oxidation in a hydrogen-rich atmosphere.

[0043] Depend on Figure 2It can be seen that with the increase of copper doping amount, the XRD patterns of the prepared precursors CuCe-BTC-FNP-Ce1Cu0.1, CuCe-BTC-FNP-Ce1Cu0.2, and CuCe-BTC-FNP-Ce1Cu0.3 show standard Ce-BTC structure diffraction peaks, and no obvious diffraction peaks of copper and its oxides are observed, indicating that the copper species is highly dispersed in the catalyst and will not affect the crystal structure of Ce (BTC).

[0044] Depend on Figure 3 It can be seen that with the increase of copper doping in the catalyst, the catalytic performance of the catalyst in CO oxidation in a hydrogen-rich atmosphere is gradually improved. When the copper doping amount rises to Ce1Cu0.2, the catalytic performance reaches the best. As the copper doping amount continues to increase, the catalytic performance gradually decreases. When the copper doping amount is Ce1Cu0.2, the CO conversion rate is 100% at a reaction temperature of 90°C, and the corresponding CO2 selectivity is also 100%. The activity test results of CuO / CeO2 catalysts prepared with different copper doping amounts in a microchannel reactor show that a moderate copper doping amount can significantly improve the low-temperature activity of the catalyst in CO oxidation in a hydrogen-rich atmosphere.

[0045] It was finally measured that the best performance was achieved when the cerium-copper ratio was 1:0.2. The CO conversion rate reached 100% at 90°C, and the corresponding selectivity was also 100%. The performance was compared with the CuO / CeO2 catalysts prepared by the solvothermal method with different solvents. The CuO / CeO2 catalyst prepared by the rapid fluid turbulent mixing method had the highest low-temperature activity for CO oxidation in a hydrogen-rich atmosphere.

[0046] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing, characterized in that: The following steps are involved: S1. Dissolve copper salt and cerium salt in a molar ratio of 1:0.1 to 1:0.3 in 80 mL of deionized water to form solution A; S2, dissolving sodium hydroxide and trimesic acid in a mass ratio of 12:7 in 80 mL of deionized water to form solution B; S3. Inject equal volumes of solution A and solution B into a fast fluid turbulent flow reactor for reaction, then take the precipitate generated in the fast fluid turbulent mixing reactor and record it as CuCe-BTC-FNP, then let the CuCe-BTC-FNP precipitate stand, centrifuge and collect the solid; vacuum dry and grind, then place the ground powder in a muffle furnace and calcine for 2 hours to obtain a catalyst, named CuCeO-FNP-Ce1CuX, where X is 0.1 to 0.

3.

2. The method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method according to claim 1, characterized in that: The copper salt is copper nitrate trihydrate.

3. The method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method according to claim 1, characterized in that: The cerium salt is cerium nitrate hexahydrate.

4. The method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method according to claim 1, characterized in that: The flow rates of solution A and solution B injected into the fast fluid turbulent mixing reactor were both 90 mL / min.

5. The method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method according to claim 1, characterized in that: The vacuum drying condition is drying at 80° C. for 12 h.

6. The method for synthesizing CuO / CeO2 catalyst by rapid fluid mixing method according to claim 1, characterized in that: The calcination temperature in the muffle furnace is 500° C., and the heating rate is 5° C. / min.

7. A CuO / CeO2 catalyst prepared by the method according to any one of claims 1 to 6.

8. Use of the CuO / CeO2 catalyst as claimed in claim 7 in catalytic oxidation removal of CO in a hydrogen-rich environment.

Citation Information

Cited By

  • Fischer-Tropsch synthesis catalyst, preparation method thereof and device for synthesizing supported catalyst

    CN116408131A

  • Fischer-Tropsch synthesis catalyst, its preparation method, and device for synthesizing supported catalyst

    CN116408131B

  • CuCe composite metal oxide rapidly prepared based on Joule heat as well as preparation method and application of CuCe composite metal oxide

    CN120900642A

  • Ce-doped Co-MOF derived CuO composite oxide catalyst and preparation method thereof

    CN121819845A

  • Sulfur-resistant CO oxidation catalyst and preparation method thereof

    CN121819880A